Functionalizing carbohydrates for food applications : texturizing and bioactive/flavor delivery systems - Embuscado, Milda E. (DEStech, 2014)
"This book, written by leading food chemists, systematically explains the chemistry and engineering of new starch-based polymers and carbohydrates and shows how they are used to improve food texture and also to function as carriers for flavors and bioac